Empowering Community Entrepreneurship Through Salt-Based Mouthwash Production - Alamsjah, Mochammad Amin; Pujiastuti, Dwi Yuli (OJS Universitas Muhammadiyah Gresik, 2025)
In this PKM program, our partner is residents in Sedayulawas, Lamongan, East Java, Province. This community has generated the production mouthwash derived from salt. Salt is a mineral composed primarily of sodium chloride (NaCl). Diversification of salt products with various derivative products is very possible for salt farmers to do as an effort to empower the economy of the Lamongan community as well as increase food security through the provision of quality salt and downstream technology to produce salt derivatives that have more value for example mouthwash. Mouthwash containing saltwater rinses work by increasing the pH- balance inside the mouth, creating a much more alkaline oral environment in which the bacteria are no longer able to thrive. Based on interviews and observations in the field, there are 3 main focuses of the problems currently faced by partners, namely: 1) lack of knowledge about downstreaming of salt products and their derivatives and 2) the packaging of product. Efforts to increase salt production and salt purification technology as well as alternative diversification of salt derivative products can be a model that can drive the economic sector of the community of salt farmers and women who boil salt so as to initiate the opening of new job opportunities and create superior salt products and derivative products, namely mouthwash in Lamongan Regency. This activity was realized with an approach in the form of making a sustainable cooperation program until the end of PKM, creating a family atmosphere between the two and understanding that the problems experienced were a shared problem so that they could be solved together according to the level of responsibility to achieve the expected benefits, namely increased yields, production and productivity and competitiveness, independence and welfare of the community.